Importance of Application of Modern Act in Physics (Texas Journal of Engineering and Technology, 2022)
This article describes the tools and technologies needed to improve the quality of the physics teaching process. The teaching of science focuses on the advantages of ICT tools and the process of their application. The lesson provides tips for engaging and engaging students